1983
DOI: 10.1084/jem.157.6.1932
|View full text |Cite
|
Sign up to set email alerts
|

Early development of the T cell repertoire. In vivo treatment of neonatal mice with anti-Ia antibodies interferes with differentiation of I-restricted T cells but not K/D-restricted T cells.

Abstract: A large number of studies have indicated that the activation of T helper cells for both antibody (1-6) and cytolytic T lymphocyte (CTL) 1 (7-11) 2 responses is restricted by products of the I region of the major histocompatibility complex (MHC), while the activation of CTL themselves is restricted by products of the K/D regions of the MHC (12-14). However, it is less clear how and when during their developmental pathway T ceils acquire their MHC-restricted self-recognition specificity. Studies with chimeras (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

1984
1984
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 38 publications
0
24
1
Order By: Relevance
“…It was previously reported that a pan-specific mAb directed at MHC class II molecules could inhibit the process of positive selection (19,20). Here, we report that an mAb directed at the complex of a self-peptide bound to self-MHC class II molecules can specifically interfere with the process of intrathymic negative selection in vivo.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…It was previously reported that a pan-specific mAb directed at MHC class II molecules could inhibit the process of positive selection (19,20). Here, we report that an mAb directed at the complex of a self-peptide bound to self-MHC class II molecules can specifically interfere with the process of intrathymic negative selection in vivo.…”
mentioning
confidence: 75%
“…Pioneering experiments using injection of anti-MHC class II mAbs into neonatal mice revealed that the development of MHC class II-restricted T cells requires their interaction with MHC class IIpositive cells in the thymus, and interference with this process has profound effects on T cell development (19). In these mice the lymphoid organs were devoid of CD8 Ϫ CD4 ϩ T cells, whereas the development of CD8 ϩ CD4 Ϫ T cells proceeded normally (20).…”
Section: Specific Interference With Intrathymic Negative Selection Immentioning
confidence: 99%
“…In fact, the evidence seems very clear that clones of T cells are actually selected positively for self-reactivity during an early differentiation step in the thymus cortex (Bevan 1977, Zinkernagel 1978, giving rise to a peripheral pool of T cells biased in favor of recognizing antigenic molecules in association with MHC allelic products to which they were exposed during their ontogeny in the thymus. At this point, it also seems clear that the specific interaction occurring during positive selection in the thymus involves the T-cell receptor complex, the CD4 and CD8 accessory molecules and thymic MHC antigens (Kruisbeeck et al 1983, McDuffie et al 1986. It is this step which seems to determine the differentiation of immature CD4+8+ thymocytes into more mature CD4+8-and CD4-8+ T cells (Teh et al 1988, Sha et al 1988.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of precursor T cells with H-2 Iabearing cells appears to be necessary for appropriate maturation of T helper cells. This, especially, suggests that thymic selection concerns class II MHC specifically (46,47). Indeed, the presence of class II (but not class I) MHC antigens on the cortical epithelium (48, 49) might suggest selection for class IIreactive cells.…”
Section: Discussionmentioning
confidence: 99%